Development of a problem-oriented index system for evaluating the integration of medical treatment and prevention at county level: a Delphi study based on the rainbow model - Cancan LI; Chengyue LI; Zijing WANG; Zhongliang BAI; Ren CHEN; Qunhong SHEN; Lingzhong XU; Chuan PU; Anning MA; Junwen GAO; Hua WANG; Mo HAO; et al. (Zhongguo gonggong weisheng)
ObjectiveTo construct an evaluation index system in accordance with the practical implementation of county-level medical treatment and prevention integration in China, and to provide guiding principles and evaluation tools for its scientific development. MethodsUsing the rainbow model as a theoretical foundation, a theoretical framework and a pool of candidate indicators for evaluating county-level medical-preventive integration were established through policy analysis and literature review. The Delphi method and analytic hierarchy process (AHP) were used to determine the index system and corresponding weights. ResultsThe response rates for the two rounds of expert consultation were 87% and 100%, respectively, with an average authority coefficient of 0.79. The coordination coefficients of the expert opinions were 0.222 and 0.359 (both P < 0.05). After two rounds of expert consultation, an evaluation index system was established, which included 6 first-level, 15 second-level, and 37 third-level indicators. ConclusionsThe construction of the index system was guided by appropriate theoretical principles, followed scientific methodology, adhered to systematic procedures, maintained rigorous processes, and produced reliable results to promote and enhance the development and sustainability of county-level medical-preventive integration in China.